The road to the winner's circle begins at the ASHRM Annual Conference!. Issue 2 (September 2015) - Venditti, Ellen Grady
<x xml:space="preserve">Abstract</x> The saying "Time flies when you're having fun" is a time‐honored expression that is part of our vernacular. Sometimes we say it in jest, tongue in cheek, when it seems a long day will never end! However, when we celebrate professional or personal anniversaries, when we look at our growing kids, or especially, when we look in the mirror, we marvel at how fast the years have flown by!